The frequency of electrodes replacement in patients undergoing cardiac resynchronizaton therapy during long term follow up. (14th October 2021) - Jedrzejczyk-Patej, E; Mazurek, M; Sokal, A; Kotalczyk, A; Gumprecht, J; Szulik, M; Pruszkowska-Skrzep, P; Kowalski, O; Lenarczyk, R; Kalarus, Z
Abstract: Background: Cardiac resynchronization therapy (CRT) is an effective method of treatment in patients with HF, but as complex device with three electrodes, it is prone to electrode dysfunctions and the need to replace them. However little is known about the frequency of need for leads replacement in subjects undergone CRT in a very long-term follow up. Aim: To determine the frequency of leads replacement in patients undergoing CRT during long term follow-up. Methods: Study population consisted of 1059 consecutive patients with CRT implanted between 2002 and 2019 in tertiary care university hospital, in a densely inhabited, urban region of Poland. The data about lead replacement was collected. Results: During the median follow-up of 1661 days (IQR: 815–2792) for non-infectious reasons (dislocation, dysfunction, fracture etc.) a total of 324 leads in 251 patients (23.7%) were replaced. Median time from CRT implantation to the first lead replacement was 359 days (42–1413). The electrode replacement within first year after CRT implantation was performed in 126 subjects (50.2%), in the rest of patients (49.8%) the leads were replaced after one year of device implantation. In patients with above ten years of follow up (n=143; 13.5%) 67 subjects (46.8%) had one or more lead replacement during follow up. Patients with electrode replacement during follow-up were younger (63 vs 66 years, P<0.001), more often with nonischemic cardiomyopathy (52.6% vs 41.6%, P=0.002), less often with permanent atrial fibrillation (12.4% vs 24.4%, P<0.001) and had higher left ventricle end-diastolic diameter (68 vs 67 mm, P=0.02). The duration of the first CRT device implantation were longer with higher fluoroscopy time in comparison with patients without lead replacement during follow up (135 vs 120 min, P<0.001 and 20.5 vs 16 min, P<0.001, respectively) and these were an independent predictors of lead replacement during FU (HR 1.002, 95% CI 1.000–1.006, P=0.03 and HR 1.005, 95% CI 1.002–1.008, P<0.001, respectively). Conclusions: The need for leads replacement due to non-infectious reasons reaches almost 25% of patients with CRT within 4.5 years. Half of the patients have lead replacement within one year after CRT implantation and the other half during long term follow up. The duration of the first procedure (CRT device implantation) is strong predictor of lead replacement during follow up. Funding Acknowledgement: Type of funding sources: None.